PELATIHAN PEMBUATAN MEDIA FLIPBOOK BAGI GURU SMA MUHAMMADIYAH SE-DKI JAKARTA - Mega Elvianasti; Agus Pambudi Dharma (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2019)
The service activities carried is training in making flipbook media for teachers in Muhammadiyah High Schools at DKI Jakarta. The partners of the service activities is Dikdasmen PWM DKI Jakarta. Based on the survey, interviews with the vice headmaster and the Secretary of the Primary and Secondary Education that there had never been a learning media training, especially flipbook and as many as 75% of teachers had never used flipbook media in learning. Based on these problems, the service activities offered offer comprehensive training starting from an understanding of media literacy, the importance of learning media, providing material about flipbook media, how to make flipbook media in accordance with the steps described and how to use flipbook media in learning. The service activity was held in January 2019. The target of the service activities was in the form of services and publications. The service coverage is in the form of material exposure regarding through flipbook media creation training. The steps taken in this service activity are : 1) Explained of material about media literacy, 2) Explained of material about learning media, 3) Explained of material about flipbook media, 4) Making flipbook media, 5) Application of flipbook media.